Application Of Reaction Speed Test Equipment in Martial Arts Sports - Lubis, Amirsyah Putra; Amansyah, Amansyah; Raswin, Raswin; Destya, Muhammad Reza (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research was carried out on advanced fighting athletes with the criteria for POPNAS, POMNAS and Pre-PON athletes in January 2024. This research aimed to produce a hand-and-foot reaction speed test tool for high-level fighting athletes and test norms for hand-and-foot reaction speed tools. The type of research used in this research is development research with research design Research & Development (R&D) from Borg and Gall. This research was carried out in 2 research stages, namely, pre-development, development and application to different groups. The population in this study used fighting athletes with POPNAS SUMUT, POMNAS SUMUT and Pre PON SUMUT degrees. The sampling technique uses purposive sampling with small trials of 20 athletes and large group trials of 30 athletes. Furthermore, a small group trial of 20 people showed a figure of 87% according to the criteria very worthy, then a large group trial of 30 athletes showed a figure of 90% by category very worthy. The results of research/feasibility tests carried out by advanced fighting trainer experts, test and measurement experts, and IT experts, show a figure of 96% in the very feasible category, so it can be used. Based on the data obtained, the development of a hand and foot reaction speed test tool in the combat martial arts sport is declared worthy of being developed as a test tool for hand and foot reaction speed in the combat martial arts sport.